Thoughts on the Structure of the European Aurignacian, with Particular Focus on Hohle Fels IV. (22nd December 2019) - Dinnis, Rob; Bessudnov, Alexander; Chiotti, Laurent; Flas, Damien; Michel, Alexandre
Abstract : Western Europe is often used as the basis from which to understand the Aurignacian of other regions. For some there is good inter-regional chronocultural agreement, whereas others see significant difference. One region frequently argued to differ is the Swabian Jura (southern Germany). In a recent contribution to this issue Bataille and Conard (2018) describe the Aurignacian assemblage from Layer IV of Hohle Fels. They convincingly outline important similarities with the Western European Late Aurignacian. However, they also argue that it is older than, and different from, the most comparable Western European assemblages, and therefore that it contradicts an Aurignacian chronocultural framework built on Western European evidence. Here we assess this claim, focusing on the sites used by Bataille and Conard in their comparison. Radiocarbon dates for Hohle Fels IV of 33–30, 000 uncal bp are no older than dates for Western European Late Aurignacian assemblages. Most of the features of Hohle Fels IV argued to demonstrate its dissimilarity are, in fact, evident in the Western European Late Aurignacian. One potential difference is the reported absence from Hohle Fels IV of microblades with inverse/alternate retouch. However, due to the near absence of laterally retouched microblades and uncertainty over whether the fine fraction has been searched we doubt the significance of this observation. Other recent publications have similarly suggested that the Western European chronocultural model is incompatible with other regions. In light of this we consider Eastern Europe. Despite some difference, reliable data point to the pene-contemporaneity of characteristic bladelet/microblade technologies between the two regions, a pattern that stratigraphies from sites across Europe are also consistent with. The biggest complicating factor is radiocarbon dating, which has created a culturally complex picture that is inconsistent with all chronostratigraphic data. We therefore offer some thoughts as to the use of radiocarbon dates for this period. Despite ongoing problems dates are still frequently presented with an unwarranted confidence in their accuracy. Their presentation should instead explicitly acknowledge the method's fallibility and its inferiority to more reliable evidence such as chronostratigraphic patterning and tephra. When radiocarbon dates contradict a consistent chronostratigraphic picture the burden of proof falls to those arguing the dates' veracity. In these cases, the reasons for the discrepancy between the radiocarbon and chronostratigraphic records require exploration.